2019
DOI: 10.1371/journal.pone.0222657
|View full text |Cite
|
Sign up to set email alerts
|

The Better Management of Patients with Osteoarthritis Program: Outcomes after evidence-based education and exercise delivered nationwide in Sweden

Abstract: We evaluated a structured education- and exercise-based self-management program for patients with knee or hip osteoarthritis (OA), using a registry-based study of data from 44,634 patients taken from the Swedish “Better Management of Patients with Osteoarthritis” registry. Outcome measures included a numeric rating scale (NRS), EuroQol five dimension scale (EQ-5D), Arthritis self-efficacy scale (ASES-pain and ASES-other symptoms), pain frequency, any use of OA medication, desire for surgery, fear–avoidance beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 43 publications
7
76
1
3
Order By: Relevance
“…From baseline to the two-year follow-up, the NRS pain scores reduced from 5.2 to 4.1, which is defined as a minimal clinical important change [ 35 ], with an ES of 0.39 ( Table 3 and Figure 1 ). These findings are in correspondence with the results both from the BOA [ 36 ], and GLA;D [ 17 ] registers, showing improvements of almost the same amount. The additional message from the present study is that the reduction in pain is maintained beyond the one-year period documented by the other registers.…”
Section: Discussionsupporting
confidence: 91%
“…From baseline to the two-year follow-up, the NRS pain scores reduced from 5.2 to 4.1, which is defined as a minimal clinical important change [ 35 ], with an ES of 0.39 ( Table 3 and Figure 1 ). These findings are in correspondence with the results both from the BOA [ 36 ], and GLA;D [ 17 ] registers, showing improvements of almost the same amount. The additional message from the present study is that the reduction in pain is maintained beyond the one-year period documented by the other registers.…”
Section: Discussionsupporting
confidence: 91%
“…Selfmanagement strategies for people with long-term conditions include patient education and behaviour modification which are designed to build people's feelings of self-efficacy and ability to set goals and take an active role in their own health outcomes and empowering them to have responsibility over the decisions and actions being made about their condition [112]. A Swedish study looking at data from over 44,000 patients with hip or knee osteoarthritis found that a structured education and exercise selfmanagement programme had a significant beneficial effect on quality of life, physical activity, pain, use of medication and sick leave [113]. While this evidence highlights the potential benefits from selfmanagement, there is a lack of research on self-management in the workplace.…”
Section: Self-managementmentioning
confidence: 99%
“…Participants in this study took part of the Supported Osteoarthritis Self-management Program (SOASP). The SOASP is recommended in clinical guidelines for the management of patients with OA in the hip, knee and hand in Sweden (35,36). The SOASP offers rst line treatment for patients with hip, knee and/or hand OA and is generally offered in primary health care.…”
Section: Settingmentioning
confidence: 99%